ANALISA KEBUTUHAN PENGEMBANGAN MATERI PECAHAN MENGGUNAKAN MEDIA PEMBELAJARAN E-LEARNING PADA SISWA KELAS V SDK FRATER XAVERIUS 2 PALEMBANG - Stefanus Christ Prayogi (Jurnal PGSD Musi, 2020)
This research was conducted to analyze the need to develop fraction material using e-learning media for fifth grade students of SDK Frater Xaverius 2 Palembang. This study adapts the research procedures of Borg and Gall. The research development developed by Borg and Gall consists of 10 stages. This article is limited to a Needs Analysis. Data collection techniques in this study used a questionnaire or questionnaire. Questionnaires or questionnaires are divided into two types, namely closed questionnaires and open questionnaires. This study uses a combination of the two questionnaires, because on the needs analysis questionnaire sheet in this study there are statements that have been accompanied by answer choices andthere are statements filled out by respondents according to actual conditions. Based on the results of the needs analysis, it is shown that the development of fractional material using elearning learning media is needed.